Mengikis Arogansi Berdakwah Melalui Pendekatan Manajemen Perencanaan Islami - Fathul Aminudin Aziz (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2019)
Da'i competence is demanded to be ready in everything. The da’i has an obligation to translate Islamic materials to the congregation properly. Recently, the tendency of a da’i to deliver da’wa material tends to be divided. Some offer peace, comfort, tranquility (rohmatal lil ‘alamien). But some others offer hatred, violence, fear, worry and so on. This kind of da'wa model indicates a serious problem with the da’i, namely